The Influence of Heat Treatment on the Static and Dynamic Sorptive Behavior of Moso Bamboo (Phyllostachys pubescens) - Yuxiang Huang; Ru Liu; Fandan Meng; Yanglun Yu; Wenji Yu (Advances in Polymer Technology)
The influence of heat treatment on moisture sorption behavior of moso bamboo (Phyllostachys pubescens), especially under dynamic sorption conditions, was investigated. Moso bamboo was heated to 180 and 200°C for 8 h to investigate the chemical components and sorptive behavior at sinusoidal relative humidity (RH) and constant humidity. The results of chemical components revealed that the content of holocellulose, α-cellulose, and hemicellulose decreased while that of lignin increased slightly with increasing treatment temperatures. The results of static adsorption at constant RH showed that 200°C treated bamboo exhibited the lowest moisture content and moisture sorption coefficient. The results of dynamic sorptive behavior indicated that the moisture content changed sinusoidally but lagged behind the triggering sinusoidal RH changes. Heat-treated bamboo presented greater phase lag and smaller amplitudes of moisture content and sorption hysteresis due to the hemicellulose removal.